The applicability of the biosafety act 2007 in addressing bioethical issues relating to genetically modified organisms (GMOs) - Idris, Siti Hafsyah; Hamin, Zaiton; Abdul Majeed, Abu Bakar (Faculty of Law, 2011)
In recent years, biotechnology has resulted in the development of a number of genetically modified organisms (GMOs). However, the introduction GMOs has led to wide debate on bioethical concerns. Such issues involved freedom of choice, ethics of interfering with nature, Islamic views on GM crops and ethical considerations of distributive justice as well as the effects of transgenic pollution to the environment (Latifah, 2010). Bioethical issue in biotechnology is an important aspect in the research stage, development stage and also the commercialization stage (Ida, 2009). The literature suggests that bioethics consideration should be included in the legal framework as the current legal regulations addressing GMOs are considerably varied less effective in discussing bioethical issues of the subject (Daniel Sperling, 2010). In Malaysia, there is no specific law on bioethics, except the Biosafety Act 2007. The law addresses all Living Modified Organisms (LMOs) with the objectives of protecting human, plant and animal health, the environment and biological diversity, and where there are threats of irreversible damage, lack of full scientific evidence may not be used as a reason not to take action to prevent such damage; and to provide for matters connected therewith. The law also recognizes the inclusion of the bioethical issues as part of the socio economic consideration under section 35. However, this law is rather vague on the bioethical issue. This project proposes to examine the applicability of the Biosafety Act 2007 in addressing bioethical issues relating to GMOs in Malaysia. Apart from that, this research also seeks to propose recommendations for the amendment to the Biosafety Act 2007 for express provision to protect bioethical issues relating to GMOs in Malaysia. Based on a qualitative research method, this project employs a case study research design in order to propose to examine the applicability of the Biosafety Act 2007 in addressing bioethical issues relating to GMOs in Malaysia.